2012
DOI: 10.1161/atvbaha.112.300302
|View full text |Cite
|
Sign up to set email alerts
|

TLR 2 Induces Vascular Smooth Muscle Cell Migration Through cAMP Response Element−Binding Protein−Mediated Interleukin-6 Production

Abstract: Objective-Migration of vascular smooth muscle cells (VSMCs) from the media into intima contributes to the development of atherosclerosis. Gene deletion experiments implicate a role for toll-like receptor 2 (TLR2) in atherogenesis. However, the underlying mechanisms remain unclear. We postulate that TLR2 promotes VSMC migration by enhancing interleukin (IL)-6 production. Methods and Results-Migration assays revealed that TLR2 agonists promoted VSMC migration but not cell proliferation or viability. TLR2 deficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 45 publications
4
41
0
Order By: Relevance
“…The contribution of TLR2 to atherosclerosis has been observed with both the TLR2-TLR1 heterodimer (Mullick et al, 2005;Qi et al, 2009;Curtiss et al, 2012) and TLR2-TLR6 heterodimer (Curtiss et al, 2012) in the two prominent animal models of atherosclerosis, apolipoprotein E (ApoE)-and LDL receptor-deficient mice. Moreover, TLR2 activation causes macrophage lipid accumulation (Kazemi et al, 2005); induces a dedifferentiated, migratory, and proliferative phenotype in vascular smooth muscle cells (de Graaf et al, 2006;Lee et al, 2012); and initiates an inflammatory reaction in endothelial cells (Triantafilou et al, 2007). Similarly, TLR4 deficiency improved indices of atherosclerosis in both ApoE- (Michelsen et al, 2004) and LDL receptordeficient mice (Ding et al, 2012).…”
Section: A Atherosclerosismentioning
confidence: 99%
“…The contribution of TLR2 to atherosclerosis has been observed with both the TLR2-TLR1 heterodimer (Mullick et al, 2005;Qi et al, 2009;Curtiss et al, 2012) and TLR2-TLR6 heterodimer (Curtiss et al, 2012) in the two prominent animal models of atherosclerosis, apolipoprotein E (ApoE)-and LDL receptor-deficient mice. Moreover, TLR2 activation causes macrophage lipid accumulation (Kazemi et al, 2005); induces a dedifferentiated, migratory, and proliferative phenotype in vascular smooth muscle cells (de Graaf et al, 2006;Lee et al, 2012); and initiates an inflammatory reaction in endothelial cells (Triantafilou et al, 2007). Similarly, TLR4 deficiency improved indices of atherosclerosis in both ApoE- (Michelsen et al, 2004) and LDL receptordeficient mice (Ding et al, 2012).…”
Section: A Atherosclerosismentioning
confidence: 99%
“…According to recent studies, TLR2 can activate p38 MAPK, ERK1/2, JNK1/2 and AKT, in vSMCs from TLR2 KO mouse. Also, cAMP response element-binding protein (CREB)-dependent IL-6 production was highly related to TLR2, not TLR4, in vSMCs migration (52). Interestingly, Lee et al suggested a new role of TLR2 in vSMCs, where MMP2 and proinflammatory cytokines can be produced through TLR2-Nox1-dependent manner, leading to increasing monocyte-endothelial cell adhesion, and transendothelial migration of monocytic cells (53).…”
Section: The Role Of Membrane Receptors Of Vsmc In Vascular Inflammationmentioning
confidence: 99%
“…MCP-1 is a potent chemoattractant that is essential in various inflammatory diseases involving the recruitment of monocytes/macrophages (33). These factors all accelerate neointimal hyperplasia by promoting the migration and proliferation of VSMCs (13,34). …”
Section: Discussionmentioning
confidence: 99%